Subcellular localization of proteins labeled with GFP in Xanthomonas citri ssp citri: targeting the division septum - Martins, Paula M. M. [UNESP]; Lau, Ivy F. [UNESP]; Bacci Junior, Mauricio [UNESP]; Belasque, Jose; do Amaral, Alexandre M.; Taboga, Sebastiao R. [UNESP]; Ferreira, Henrique [UNESP] (Wiley-Blackwell, 2010)
Xanthomonas citri ssp. citri (Xac) is the causal agent of citrus canker, an economically important disease that affects citrus worldwide. To initiate the characterization of essential biological processes of Xac, we constructed integrative plasmids for the ectopic expression of green fluorescent protein (GFP)-labeled proteins within this bacterium. Here, we show that the disruption of the alpha-amylase gene (amy), the site of plasmid integration into the bacterial chromosome, does not alter its pathogenesis while abolishing completely the ability of Xac to degrade starch. Furthermore, our GFP expression system was used to characterize ORF XAC3408, a hypothetical protein encoded by Xac that shares significant homology to the FtsZ-stabilizing factor ZapA from Bacillus subtilis (ZapABsu). GFP-XAC3408 expressed in Xac exhibited a septal localization pattern typical of GFP-ZapABsu, which indicates that XAC3408 is the Xac orthologue of the cell division protein ZapABsu. The results demonstrate the potential of GFP labeling for protein functional characterizations in Xac, and, in addition, the Xac mutant strain labeled at the septum constitutes a biological model for the exploration of antibacterial compounds able to inhibit cell division in this plant pathogen.
Keywords: citrus canker; cell division; alpha-amylase